Member Perceptions of the One Health Initiative at a Zoological Institution - Padda, Hannah; Niedbalski, Amy; Tate, Erin; Deem, Sharon L. (Frontiers in Veterinary Science, 2018)
Zoological institutions play an important role in promoting the goals of the One Health movement. We launched the Institute for Conservation Medicine (ICM) at the Saint Louis Zoo in 2011 to advance the goals of One Health. In 2016, we distributed a survey to Zoo members to evaluate member awareness and understanding of One Health and to provide direction for future communication and actions from the ICM. We hypothesized that Zoo members would be aware of One Health and care about infectious disease issues. Survey results showed Zoo members primarily cared about chronic, non-infectious diseases and their associated economic costs, with participants ranking their top three health issues of concern for humans as nutrition/obesity/diet (49%), costs of health care (48%), and cancer (37%). Zoo members were interested in the roles of zoos in One Health and found them important, but were less aware of the Saint Louis Zoo’s actions that did not directly relate to animal welfare. Only 6% of members had awareness of the term “One Health” and 16% were aware of the term “Conservation Medicine.” These results suggest that zoos may do better to tailor One Health messaging to align with member interests. Messaging and programming from the Saint Louis Zoo will now include the direct benefits to human health that zoos offer, in addition to the ICM’s more ecologically focused activities. This study offered valuable insight into how Zoo members view One Health and may serve as a template to help zoological institutions develop and promote One Health.